FORMATION OF RESEARCH COMPETENCE OF STUDENTS AT THE PROCESS OF STUDYING THE VISCOSITY OF A LIQUID - Akzholova , A.; V.; Abdulayeva, A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article examines the goals and objectives of the methodology for forming the research competence of students, using the example of the study of the internal viscosity coefficient of a liquid. The results of the study allowed us to establish components of subject research competence and find out its main structural elements - the readiness, ability of students to perform educational research, following the stages of organizing research activities, which are based on the logic of implementation of a research project. The practical implementation of the formation of this competence is one of the topical issues of educational practice of the pedagogical University, since its results deepen, expand and specify modern ideas about the information and communication capabilities of cognitive activity of students.